What types of support are required to help managers of third sector organisations become managers of social enterprises and what is the role for business advisors within this transition? - Stevenson-Dodd, Matthew David (2006)
Examines the support requirements for managers of third sector organisations wishing to make the transition towards social enterprise. Managers of emerging and established social enterprises were surveyed along with business advisors across the United Kingdom. The research demonstrated that the types of support which are required to help managers of third sector organisations become managers of social enterprises are generally wider than the services offered by traditional business advice services.